The Effect of Financial Distress and Company Characteristics on Earnings Management with the Audit Committee as Moderator - Afni, Nurul; Setiany, Erna (Journal of Economics, Finance and Accounting Studies, 2023)
The purpose of this study is to examine and analyze the effect of financial distress, operating cash flow, and return on equity on earnings management in publicly listed companies in the manufacturing industry listed on the Indonesia Stock Exchange for the period 2018-2020. To examine and analyze the influence of the audit committee moderation variable to strengthen or weaken the effect of financial distress, operating cash flow, and return on equity on earnings management in publicly listed companies in the manufacturing industry listed on the Indonesia Stock Exchange for the period 2018 – 2020. The method used is a quantitative method with an explanatory research type. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2020, a total of 150 companies. Determining the number of samples was carried out using a purposive sampling technique, and it was determined that there were 77 companies. The data analysis method used is panel data analysis with the Eviews software program version 10. The results show that financial distress has a positive effect on earnings management in Manufacturing companies listed on the IDX for the period 2018 - 2020. Operating cash flow has no effect on earnings management in Manufacturing companies listed on the IDX for the 2018 - 2020 period. Return on equity has no effect on earnings management in Manufacturing companies listed on the IDX for the 2018 - 2020 period. The audit committee is unable to moderate the effect of financial distress on earnings management in Manufacturing companies listed on the IDX for the 2018 period - 2020. The audit committee is unable to moderate and weaken the effect of operating cash flow on earnings management in Manufacturing companies listed on the IDX for the period 2018 - 2020. The audit committee is able to moderate and strengthen the effect of return on equity on earnings management in Manufacturing companies listed on the IDX period 2018 - 2020.